Electronic plastic waste management in Malaysia: The potential of waste to energy conversion - Othman N.; Mohd Sidek L.; Ahmad Basri N.E.; Muhd Yunus M.N.; Othman N.A. (2023)
The production of electronic products is one of the world's fasting growing industries today. Due to this phenomena, the amount of electronic waste generated increases proportionately with the production. The growing numbers of uses of plastic products in this sector contribute to electronic plastic waste generated. From the management of solid waste aspect, the production of electronic plastic waste has to be handled effectively. Generally, there are three options for electronic plastic waste recycling which is chemical, mechanical or thermal recycling. The main purpose of this paper is to discuss the research conducted on electronic plastic waste which consisted of various types of resin to determine the electronic plastic waste's potential as a source of energy. The physical and chemical characteristics of the electronic plastic waste are determined by the proximate analysis, ultimate analysis and the heavy metal content analysis of the plastic waste resin sample. The dulong formula was applied to calculate the heating value of electronic plastic waste based on the data obtained from the ultimate analysis. The result shows that the average heat value for an electronic waste is 30, 872.42 kj/kg or 7, 375 kcal/kg. The emmission factor analysis shows the concentration of air emission value which would probably be formed due to incineration activitiy is less than the effluent parameter of standard A and standard B limits fixed by the environmental quality act (clean air) 1978 for control air pollution. Basically, this research has succeeded in proving the potential of electronic plastic waste to be used as a source of energy in the future. 2009 IEEE.